Do men know which lower bowel symptoms warrant medical attention? A web-based video vignette survey of men in Western Australia - Oberoi, Devesh Varun; Jiwa, Moyez; McManus, Alexandra; Parsons, Richard (SAGE Publication, 2015)
The current study aims to explor how men would advise other men about seeking help for lower bowel symptoms and also to determine the factors that may influence help seeking. A purposive sample of Western Australian men aged 18 years and older was recruited for the study. Participants completed 8 of the 28 randomly assigned video vignettes (video clips) displaying men (older or younger) with various combinations of one or more lower bowel symptoms. Participants were asked if the person in the vignette should seek health advice. Subsequently, the participants answered a set of questions based on the Health Belief Model. A total of 408 participants (response rate = 51%) answered 3,264 vignettes. Participants younger than 50 years, participants who were not tertiary educated and those who had lower incomes, or those living in regional or remote areas were less likely to advise help seeking from general practitioner (GP). Participants who visited their general practitioner less frequently were also less likely to advise help seeking. There was a trend to consider unintentional weight loss and diarrhea as minor symptoms not necessitating medical attention compared with rectal bleeding. The findings suggest for a need to improve public awareness among men about the need to seek timely medical advice for lower bowel symptoms in primary care. The importance of early presentation of persistent lower bowel symptoms must be specifically targeted at men younger than 50 years, those with lower incomes, or residing in regional or remote areas.